Effectiveness of Health Educational Program on Mothers¶ Practices toward care of Children with Squint of Eyes at Ibn Al- Haitham Teaching Eye Hospital in Baghdad City - Asad Allah Mahday, Zainab; Hassoon Khudhair, Suad (International Journal of Psychosocial Rehabilitation, 2020)
Objectives: The study aims to determine effectiveness of health educational program on mothers practices toward care of children with squint at Ibn Al- Haitham teaching eyes hospital in Baghdad city.Methodology: A quasi –experimental study design two- group (pre-test, post-test 1 and post-test 2) conducted at Ibn Al- Haitham teaching eyes hospital in Baghdad city during the period from 25 October 2019 to 20 August 2020. And that by collecting (100) samples from mothers' participants. This study exposed to the educational program only.Results: Results showed a clear positive impact of the program on mothers practices towards children with squint. It indicated high significant differences for this group between the pre-test and the post-test in the main aspects that have to do with the mothers practices about children with squint.Recommendations: the study recommends that the educational lectures should conducted & regularly updated for mothers toward care of children with squint of eyes for those who coming at hospital always. It also recommended more research studies should conducted on a larger sample & more of hospital in other of Iraqi governorates.